Lessons learned from 25 years with telemedicine in Northern Norway - Hartvigsen, Gunnar; Pedersen, Steinar (University Hospital of North Norway, Norwegian Centre for Integrated Care and Telemedicine, 2015)
Published version, also available at https://ehealthresearch.no/ . The pdf-file was swapped with a new version with minor corrections, 2. August 2017. A russian language version of this book is available at http://hdl.handle.net/10037/11269